THE INFLUENCE OF TEACHER PERFORMANCE ACHIEVEMENTS, TEACHING FACILITIES, SCHOOL PRINCIPAL SUPERVISION ON THE QUALITY OF GRADUATES AND ACCREDITATION - Suherning, Dina; Sugilar, Sugilar; Kurniatun, Taufani C. (Universitas Pendidikan Indonesia, 2024)
This research aims to describe the achievement of teacher performance, teaching facilities, and school principal supervision that can influence the quality of graduates and school accreditation. The research method used in this study is the inferential statistical analysis method using a quantitative approach, examined using the causal relationship method and the data is analyzed using Structural Equation Modeling (SEM) using the Smart PLS application to obtain significant interrelated results. The results of this study indicate that the variables of Teacher Performance Achievement and Teaching Facilities have a significant effect on Graduate Quality, while School Principal Supervision does not have a significant effect on Graduate Quality. Teacher Performance Achievement, Teaching Facilities, and School Principal Supervision do not have a significant effect on School Accreditation, while Graduate Quality has a significant effect on School Accreditation. Teacher Performance Achievement, Teaching Facilities, and School Principal Supervision simultaneously do not have a significant effect on Graduate Quality, and Teacher Performance Achievement, Teaching Facilities, School Principal Supervision, and Graduate Quality simultaneously do not have a significant effect on School Accreditation. This research is expected to have an impact on the development of teacher performance carried out consistently as well as the maintenance of teaching facilities in the school environment.